Barriers to sustainable green innovation in meeting the challenges of the global economy of firms - A. Escobar; J. Luna; A. Caraballo (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Sustainable innovation is crucial, because it is a key strategy for ensuring the long-term survival of companies in a world with limited resources. Consequently, understanding the barriers faced by companies in achieving sustainable innovation, such as high initial cost, lack of technical knowledge, or unclear regulations, is important for developing appropriate policies, strategies, and solutions that promote and facilitate its adoption.METHODS: This study aims to analyze the relevant and most important scientific evidence and research topics on barriers to sustainable innovation through a bibliometric analysis combined with concurrence networks and cluster analysis using VOSViewer.FINDINGS: Research on barriers to innovation was developed on a larger scale in 2012 with an average growth of approximately 43 percent until 2022. During this period, the study on green innovation has been predominant and on the social component of sustainable innovation to a lesser extent. Asia, specifically China, is leading the research on this topic mainly on the environmental component of sustainable innovation. In terms of barriers, the majority of the literature focus on financial constraints. The research agenda focus on the following areas or clusters: sustainability, barriers to sustainable innovation, and social innovation.CONCLUSION: The major barriers to sustainable innovation are financial and government regulations. The current research tackles the environmental component of sustainable innovation. Therefore, future research should focus on market and knowledge barriers in developed and less developing countries and on the social component of sustainable innovation. Potential areas of research (which are underexplored) exist and can be important for future research on enhancing knowledge about barriers to sustainable innovation: applied research that considers regional effects and country-specific analysis, in particular in developing countries. Research on the social component of sustainable innovation could be relevant. Social innovation is essential, because it addresses concrete societal problems and promotes collective action and inclusion in novel ways within companies.